2023
DOI: 10.3390/app14010289
|View full text |Cite
|
Sign up to set email alerts
|

Fault Feature Extraction of Parallel-Axis Gearbox Based on IDBO-VMD and t-SNE

Zhen Wang,
Shuaiyu Wang,
Yiyang Cheng

Abstract: For the problem that the fault states of parallel shaft gearboxes are difficult to identify, a diagnostic method is proposed to optimize variational modal decomposition (VMD) and t-distributed stochastic neighbor embedding (t-SNE) using an improved dung beetle optimization algorithm I have checked and revised all. (IDBO). IDBO is obtained by amplifying dung beetle optimization (DBO) using strategies such as chaos mapping, Levy flight policy, and dynamic adaptive weighting. IDBO is employed to optimize VMD, ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…If the dung beetle encounters an obstacle and cannot move normally, it needs to simulate a dance behavior to change its direction of movement. A tangent function is used to obtain a new direction of movement, and the position update is shown in Formula (14).…”
Section: Dung Beetle Optimization Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…If the dung beetle encounters an obstacle and cannot move normally, it needs to simulate a dance behavior to change its direction of movement. A tangent function is used to obtain a new direction of movement, and the position update is shown in Formula (14).…”
Section: Dung Beetle Optimization Algorithmmentioning
confidence: 99%
“…M. Wang et al 13 optimized VMD parameters based on sparrow search algorithm and combined them with support vector machine (SVM) to diagnose bearing fault signals, achieving good results. Z. Wang et al 14 proposed an improved DBO algorithm that enhances the global search ability of the algorithm and applied it to optimize the VMD algorithm. Experimental results have shown that the optimized VMD algorithm can effectively perform modal decomposition on fault signals.…”
Section: Introductionmentioning
confidence: 99%